An investigation on oral Lichen plannus prevalence among patients with B and C hepatitis - Agha Hosseini F; Bayat N (Tehran University of Medical Sciences, 2003)
Statement of Problelem: Lichen plannus is a relatively common mucotanous disorder, due to accompanying"nburning sensation and pain in addition to its malignant transformation, has potential importance. On the other"nhand, B and C hepatitis are of the five most common death causes, resulting in significant disease spread"nproblems among dentists. As a result, the relationship between these two disorders has been recently"ninvestigated."nPurpose: The aim of the present study was to investigate the oral Lichen plannus prevalence among patients"nwith B and C hepatitis."nMaterial and Methods: In this case series study, 500 patients with B, C hepatitis, 3 04 female and 369 male"nwith the mean age of 39.09±13.13 (the youngest was 4 and the oldest was 72 years old), who referred to the"nhepatitis center of Shariati hospital, Transfusion organization and Hemophilia center, from August 2001 to"nAugust 2002, were evaluated. The information about all white lesions that couldn't be scraped was recorded"non a questionnaire for each patient. To analyze the data, t and Fisher tests were used."nResults: Two hundred and eighty nine patients were MBS Ag" 223 were HCVAb", 12 were positive for both"ntypes of hepatitis and 23 were cyrotic. From among these patients, 3 subjects were with oral Lichen plannus"n(0.6%), one belonged to HBS Ag1 group (0.35%), (P=0.38) and two patients belonged to HCV Ab' (0.9%),"n(P=0.44). These results showed no statistically significant relationship between Lichen plannus and B, C"nhepatitis. Two cyrotic patients from among 23 were with LP, which statistically was significant (P<0.05)."nConclusion: All patients with LP should be tested for B, C hepatitis and liver enzymes.